Писцы, переводчики, певчие хурритской Аррапхи (XV-XIV вв. до. н.э.) - Янковская, H. Б. (1986)
Jankovskaja, N. ?. = Jankowska N., Scribes, Interpreters, and Singers at ?urrian Arrap?e (15th-14th Centuries B.C.); ?.239-241 : engl. Résumé